The Uses of Whiteboard Animation Technique as Supplement for Scientific Course: The Case of Non-Primary School Education Students in Indonesia - Indriasih, Aini; Sumiyati, Sri; Hariyono, Mohamad; Prayitno, Edi; Sumaji, Sumaji (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research aims to find out the learning media product specifications based on Video Scribe Whiteboard Animation in terms of effectiveness, efficiency, and product attractiveness for the tutors and students. The applied method was testing the distinguishing power with the non-primary school education students of the Opened University at UPBJJ Semarang, exactly in Pati Learning Group by using the applied media for the students who took the scientific article writing course. They were explored with questionnaire. The applied data analysis was distinguishing power with stratified experimental test for the students and the field test for the non-primary education students. The results showed the product specification development was valid. It was indicated by all indicators that provided valid and reliable criteria. Secondly, the applied media was effective based on the obtained percentage, 80%. It showed most students understood the video materials and they understood the content from the media. This result was found both in pretest and posttest groups. Third, there was the influence of Video Scribe Whiteboard Animation-based learning media toward the scientific article writing material understanding. The research limitations were such as the difficulties to control the respondents while filling the questionnaire. It was because the questionnaire was filled simultaneously by the students so the results would have bias risks.